2021
DOI: 10.1002/ccr3.3997
|View full text |Cite
|
Sign up to set email alerts
|

Response to pegylated interferon in a COVID‐19–positive elderly woman with primary myelofibrosis treated with ruxolitinib

Abstract: An 83‐year‐old female had asymptomatic SARS‐CoV‐2 infection while taking ruxolitinib. She remained RT‐PCR positive for viral RNA for >120 days, and Pegylated interferon for 4 weeks led to viral RNA clearance. The observations support combination therapy of ruxolitinib + interferon for COVID‐19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 76 publications
(98 reference statements)
0
3
0
1
Order By: Relevance
“…A total of 178 studies were found to have reported IFNα treatment for COVID-19 (Supplemental 2). [13] , [17] , [19] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , …”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsunclassified
See 2 more Smart Citations
“…A total of 178 studies were found to have reported IFNα treatment for COVID-19 (Supplemental 2). [13] , [17] , [19] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , …”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsunclassified
“…The use of IFNα inhalation was reported in patients with various comorbidities and conditions, including patients with atopic dermatitis, [38] allergic rhinitis, [38] bronchiolitis, [25] chronic obstructive pulmonary disease, [84] , [162] tuberculosis, [55] cardiovascular disease, [22] hypertension, [22] , [84] , [150] , [162] diabetes, [32] , [39] hyperlipidemia, [150] obesity, [126] metabolic syndrome, [192] chronic hepatitis B infection, [76] , [153] chronic kidney disease, [22] , [70] malignancy, [163] liver transplant, [50] kidney transplant, [70] , [172] and pregnancy. [19] The use of subcutaneous injection of IFNα was reported in patients with diabetes, [42] hypertension, [42] , [44] hyperlipidemia, 42 chronic hepatitis B infection, [140] primary myelofibrosis with macrocytic anemia, [44] dementia, [44] chronic kidney disease, [44] Behcet's disease, [190] and osteoporosis. [44] However, whether IFNα treatment is safe and efficacious in COVID-19 patients with these comorbidities requires further clinical studies.…”
Section: Comprehensive Review Of the Literature On The Safety And Efficacy Of Interferon Alpha Treatment In Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early administration of monoclonal antibodies to the spike protein, RNA‐dependent RNA polymerase inhibitor remdesivir and dexamethasone and late administration of enoxaparin may modify the natural history of the infection, 11‐15 but additional treatments are needed. We previously reported the activity of a ruxolitinib plus interferon combination 16 . In this case report, we examine another combination that may show utility for SARS‐CoV‐2 infections.…”
Section: Introductionmentioning
confidence: 99%